Bioplastik Berbasis Pati Sagu dengan Penambahan Filler Microfibrillated Cellulose dan Refuse-Derived Fuel - Khairunisa Betariani; Puji Rahayu; Winda Sri Jaman; Mohammad Wirandi (Universitas Darul Ulum, 2025)
This study aims to develop starch-based bioplastics using sago starch with the addition of Microfibrillated Cellulose (MFC) and Refuse-Derived Fuel (RDF) fillers to enhance mechanical properties and material sustainability. Sago starch was selected as the base material due to its biodegradability, while MFC derived from empty palm oil fruit bunches served as a structural reinforcement, and RDF was introduced as an additional filler sourced from processed organic and inorganic waste. The bioplastic production process involved starch gelatinization, mixing with MFC and RDF solutions, addition of sorbitol as a plasticizer, casting, and natural drying. Characterization included morphological analysis and mechanical testing. Results showed that the sago starch+MFC bioplastic exhibited a more homogeneous surface morphology and superior mechanical properties, with a maximum tensile strength of 10.6 MPa and elongation at break of 5.7%. The addition of RDF increased material density but reduced homogeneity and toughness, with fracture energy per volume drastically decreasing from 488.28 kJ/m³ to 41.15 kJ/m³. Overall, the combination of sago starch and MFC offered better mechanical performance, while RDF addition requires optimization to maintain structural integrity. This innovation supports waste utilization and promotes circular economy principles in the development of environmentally friendly materials.